2013
DOI: 10.1038/ki.2013.68
|View full text |Cite
|
Sign up to set email alerts
|

Bax and Bak have critical roles in ischemic acute kidney injury in global and proximal tubule–specific knockout mouse models

Abstract: Bax and Bak, two pro-apoptotic Bcl-2 family proteins, have been implicated in acute kidney injury following renal ischemia/reperfusion; however, definitive evidence for a role of these genes in the disease process is lacking. Here we first examined two Bax-deficient mouse models and found that only conditional Bax-deletion specifically from proximal tubules could ameliorate ischemic acute kidney injury. Global (whole mouse) knockout of Bax enhanced neutrophil infiltration without significant effect on kidney i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 42 publications
2
106
1
2
Order By: Relevance
“…Systemic deletion of Bax enhanced neutrophil infiltration without significant effect on kidney injury. 27 Our data indicate that expression of Bax, Bid, and Siva are induced in ischemic kidneys but attenuated in p53 KO mice. The significance of Bid and Siva expression in IRI was previously reported.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Systemic deletion of Bax enhanced neutrophil infiltration without significant effect on kidney injury. 27 Our data indicate that expression of Bax, Bid, and Siva are induced in ischemic kidneys but attenuated in p53 KO mice. The significance of Bid and Siva expression in IRI was previously reported.…”
Section: Discussionmentioning
confidence: 58%
“…p53 can upregulate the expression of several proapoptotic genes, including Bax, Fas/Apo-1, PERP, Siva, PUMA, and Noxa, under stress situations. 16 Recently, Dong and colleagues, 27 using two Bax-deficient mouse models, found that only conditional Bax deletion specifically from PTs could ameliorate IRI. Systemic deletion of Bax enhanced neutrophil infiltration without significant effect on kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…28,37 Remarkably, deletion of apoptotic genes specifically from proximal tubules results in marked decreases in apoptosis and protection from both ischemic and nephrotoxic AKI. 38,39 Together, these studies show an important role of tubular cell apoptosis in AKI.…”
Section: Apoptosis-the Classic View Of Regulated Cell Death In the Kimentioning
confidence: 96%
“…Mitochondrial dynamics have emerged as an important aspect in AKI cellular injury (46). Mitochondrial fission occurs during stress or cell ischemic injury, leading to enhanced BAX/BAK sensitivity and apoptosis (47)(48)(49). Additionally, there is marked upregulation (50, 51) of apoptotic regulators (p53) (5,52), initiators (caspases) (53)(54)(55), and protective genes (heme oxygenase, refs.…”
Section: Proximal Tubule Cellsmentioning
confidence: 99%